2009
DOI: 10.1136/gut.2009.178558
|View full text |Cite
|
Sign up to set email alerts
|

Anti-interleukin-5 antibody treatment (mepolizumab) in active eosinophilic oesophagitis: a randomised, placebo-controlled, double-blind trial

Abstract: Objective: Eosinophilic oesophagitis (EoO) is a clinicopathological condition defined by proton pump inhibitorrefractory oesophageal symptoms combined with oesophageal eosinophilia. The pharmacodynamic effect of mepolizumab (a humanised anti-interleukin-5 monoclonal antibody) in EoO was evaluated. Methods: Eleven adults with active EoO (.20 peak eosinophil number/high power field (hpf) and dysphagia) were randomised to 750 mg of mepolizumab (n = 5) or placebo (n = 6) and received two intravenous infusions, 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
385
0
20

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(408 citation statements)
references
References 43 publications
3
385
0
20
Order By: Relevance
“…Among the interventional trials (randomized controlled trial studies [RCTs] or trials with historical controls), 80 (80%) compared treatment effect using histological remission as values within the range of 0 to ≤5 eosinophils/hpf. Among studies that examined the effectiveness of monoclonal antibody treatment in EoE subjects, 80% defined histological remission as peak esophageal eosinophil counts within the range of 0 to ≤5 24, 25, 26, 27, 28. Approximately 26% (N = 15) of the eligible studies examined remission among EoE patients who received only the diet elimination treatment formula (SFED, FFGED, ELED) compared to other forms of treatment, with the most common definitions falling within 0 to ≤5 eosinophils/hpf 29, 30, 31, 32, 33, 34 or 11 to ≤15 eosinophils/hpf 35, 36, 37, 38, 39, 40.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the interventional trials (randomized controlled trial studies [RCTs] or trials with historical controls), 80 (80%) compared treatment effect using histological remission as values within the range of 0 to ≤5 eosinophils/hpf. Among studies that examined the effectiveness of monoclonal antibody treatment in EoE subjects, 80% defined histological remission as peak esophageal eosinophil counts within the range of 0 to ≤5 24, 25, 26, 27, 28. Approximately 26% (N = 15) of the eligible studies examined remission among EoE patients who received only the diet elimination treatment formula (SFED, FFGED, ELED) compared to other forms of treatment, with the most common definitions falling within 0 to ≤5 eosinophils/hpf 29, 30, 31, 32, 33, 34 or 11 to ≤15 eosinophils/hpf 35, 36, 37, 38, 39, 40.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 22 studies selected from European centers, 12 studies (55%) considered values within the range 11 to ≤15 eosinophils/hpf 17, 36, 37, 38, 39, 46, 47, 53, 54, 55, 56, 57, 58 as histological remission, and 4 studies (23%) defined histological remission as less than 5 or ≤ 5 eosinophils/hpf 30, 33, 42, 45. Strikingly, all studies conducted in Switzerland used a more stringent and consistent end‐point of <5 eosinophils /hpf to identify cases of histological remission 28, 59, 60…”
Section: Resultsmentioning
confidence: 99%
“…An initial open labeled trial of 4 patients in 2006 receiving mepolizumab, showed both a reduced esophageal eosinophilic count and improvement in symptoms. Two larger trials including a RCT of 59 children receiving mepolizumab, showed a decrease in eosinophilic count, however not a significant change in symptoms [64][65][66]. In a 2012 study, 226 children and adolescents with EoE were given reslizumab with significant improvement in intraepithelial esophageal eosinophil counts.…”
Section: Biological Agentsmentioning
confidence: 99%
“…Although the monoclonal antibody against IL-5, mepolizumab is approved for asthma with an eosinophilic phenotype, and studies have considered its use for eosinophilic esophagitis [111]. Limited studies demonstrate that mepolizumab reduces intraepithelial eosinophils in children and adults, though efficacy with reducing symptoms is lacking [112,113].…”
Section: Eosinophilic Esophagitismentioning
confidence: 99%